KEDUDUKAN SAKSI KETIKA MENJATUHKAN TALAK - Ahmad Syauki (Musyarokah: Jurnal Hukum dan Ekonomi Islam, 2025)
Divorce is the breaking up of a family because one or both partners decide to leave each other so that they stop carrying out their obligations as husband and wife or release the bonds of marriage and the end of the husband and wife relationship for a certain time or forever. Among the existing problems is about the position of witnesses in divorce, there are differences of opinion among scholars, some are obligatory and some are not. In this problem, the author will analyze the position of witnesses when issuing divorce using the qiyas approach. The method that will be used in this study is normative research that focuses on the analysis of existing legal regulations. In this study, a law will be produced from the results of qiyas between presenting witnesses in marriage and divorce which in conclusion both produce mandatory laws in presenting witnesses.